2014
DOI: 10.1002/glia.22764
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted glial restricted precursor cells improve neurobehavioral and neuropathological outcomes in a mouse model of neonatal white matter injury despite limited cell survival

Abstract: Objective Neonatal White Matter Injury (NWMI) is the leading cause of cerebral palsy and other neurocognitive deficits in prematurely-born children, and no restorative therapies exist. Our objective was to determine the fate and effect of glial restricted precursor cell (GRP) transplantation in an ischemic mouse model of NWMI. Methods Neonatal CD-1 mice underwent unilateral carotid artery ligation on postnatal-day 5 (P5). At P22, intracallosal injections of either eGFP+ GRPs or saline were performed in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
(63 reference statements)
0
28
0
Order By: Relevance
“…These findings suggest that perinatal HI alters development through a delay in maturation of affected cell types, including neurons and oligodendroglia (2,21,22). Behavioral deficits are associated with white matter injury, as well as the expression of MBP in white matter (23,28,29).…”
Section: Discussionmentioning
confidence: 95%
“…These findings suggest that perinatal HI alters development through a delay in maturation of affected cell types, including neurons and oligodendroglia (2,21,22). Behavioral deficits are associated with white matter injury, as well as the expression of MBP in white matter (23,28,29).…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, our group recently showed that GRPs are able to improve structural as well as functional outcomes in a mouse model of ischemic neonatal white matter injury [18]. Despite these encouraging results, the mechanisms by which transplanted GRPs ameliorate outcome remain poorly understood FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, none of the described studies was conducted in neonates, whose brain displays its own characteristic environment that is barely comparable to that of the adult. Thus, although we used native GRPs in our previous [18] as well as in the current study, future investigations comparing different preparations of transplantable cells in the context of a newborn, developing brain will be highly relevant in the transition process from pre-clinical to clinical studies. Importantly, even the slightest possibility of pain or a similar adversity has to be excluded before the step from bench to bedside can safely be made.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of evidence gained from the studies on animal models supports that the goal seems to be achievable, although a great deal of investigation is to be done and efficient sources of stem cells for OPC generation are needed. Oligodendrocyte progenitor engraftments into hypomyelinated shiverer mice [Cristofanilli et al, 2011;Wang et al, 2013], demyelinated spinal cord [Cao et al, 2010;Keirstead et al, 2005;, brain injured by hypoxia-ischemia [Chen et al, 2015;Porambo et al, 2015] or inflamed rat retina [Arriola et al, 2010;Setzu et al, 2004] have been shown to trigger graft-derived myelination, although the remyelination in chronically demyelinated lesions present in such diseases as multiple sclerosis (MS) or after spinal cord injury (SCI) still remains a challenge [Foote and Blakemore, 2005;Nazm Bojnordi et al, 2014;Podbielska et al, 2013;Tanaka and Yoshida, 2014]. The above mentioned beneficial role of oligodendrocytes conferred due to the secreted factors modulating the locally ongoing processes is likely to contribute efficiently to designing therapeutic approaches based on OPC transplantation.…”
Section: Beneficial Role Of Oligodendrocytesmentioning
confidence: 99%